Convergences and Divergences of Thymus- and Peripherally Derived Regulatory T Cells in Cancer - BUROCCHI, ALESSIA; COLOMBO, MARIO P.; PICONESE, Silvia (Frontiers in Immunology, 2013)
The expansion of regulatory T cells (Treg) is a common event characterizing the vast majority of human and experimental tumors and it is now well established that Treg represent a crucial hurdle for a successful immunotherapy. Treg are currently classified, according to their origin, into thymus-derived Treg (tTreg) or peripherally induced Treg (pTreg) cells. Controversy exists over the prevalent mechanism accounting for Treg expansion in tumors, since both tTreg proliferation and de novo pTreg differentiation may occur. Since tTreg and pTreg are believed as preferentially self-specific or broadly directed to non-self and tumor-specific antigens, respectively, the balance between tTreg and pTreg accumulation may impact on the repertoire of antigen specificities recognized by Treg in tumors. The prevalence of tTreg or pTreg may also affect the outcome of immunotherapies based on tumor-antigen vaccination or Treg depletion. The mechanisms dictating pTreg induction or tTreg expansion/stability are a matter of intense investigation and the most recent results depict a complex landscape. Indeed, selected Treg subsets may display peculiar characteristics in terms of stability, suppressive function, and cytokine production, depending on microenvironmental signals. These features may be differentially distributed between pTreg and tTreg and may significantly affect the possibility of manipulating Treg in cancer therapy. We propose here that innovative immunotherapeutic strategies may be directed at diverting unstable/uncommitted Treg, mostly enriched in the pTreg pool, into tumor-specific effectors, while preserving systemic immune tolerance ensured by self-specific tTreg.